Growth Hormone and Insulin-like Growth Factor-I Molecular Weight Isoform Responses to Resistance Exercise Are Sex-Dependent - Pierce, Joseph R.; Martin, Brian J.; Rarick, Kevin R.; Alemany, Joseph A.; Staab, Jeffery S.; Kraemer, William J.; Hymer, Wesley C.; Nindl, Bradley C. (Frontiers in Endocrinology, 2020)
Purpose To determine if acute resistance exercise-induced increases in growth hormone (GH) and insulin-like growth factor-I (IGF-I) were differentially responsive for one or more molecular weight (MW) isoforms and if these responses were sex-dependent. Methods College-aged men (n=10) and women (n=10) performed an acute resistance exercise test (ARET; 6 sets, 10 repetition maximum (10-RM) squat, 2-min inter-set rest). Serum aliquots from blood drawn Pre-, Mid-, and Post-ARET (0, +15, and +30-min post) were processed using High Performance Liquid Chromatography (HPLC) fractionation and pooled into 3 MW fractions (Fr.A: >60; Fr.B: 30-60; Fr.C: <30 kDa). Results We observed a hierarchy of serum protein collected among GH fractions across all time points independent of sex (Fr.C > Fr.A > Fr.B, p≤0.03). Sex×time interactions indicated that women experienced earlier and augmented increases in all serum GH MW isoform fraction pools (p<0.05); however, men demonstrated delayed and sustained GH elevations (p<0.01) in all fractions through +30-min of recovery. Similarly, we observed a sex-independent hierarchy among IGF-I MW fraction pools (Fr.A > Fr.B > Fr.C, p≤0.01). Furthermore, we observed increases in IGF-I Fr. A (ternary complexes) in men only (p≤0.05), and increases in Fr.C (free/unbound IGF-I) in women only (p≤0.05) vs. baseline, respectively. Conclusions These data indicate that the processing of GH and IGF-I isoforms from the somatotrophs and hepatocytes are differential in their response to strenuous resistance exercise and reflect both temporal and sex-related differences.